The effectiveness of telemarketing in promoting streamyx package / Nurulhuda Ramli - Ramli, Nurulhuda (2011)
The purpose of this research was to identify the effectiveness of telemarketing in promoting Streamyx package. Currently, Telekom Malaysia Berhad ™ is among the best telecommunication industry in Malaysia. TM is wanted to maintain it competitiveness in the market. To achieve it, Telekom Malaysia Berhad used telemarketing in promoting it successfully product, Streamyx. Researcher is used probability and non-probability sampling technique, where 75 questionnaires are distributed to the respondents who lived in Terengganu. The researcher measured dependant variable effectiveness of telemarketing in promoting Streamyx package and three independent variables which were attitude of caller, time management and prior cold calling. The findings are interpreted by using frequency distribution analysis, descriptive analysis and hypothesis testing. The findings in descriptive analysis showed that all variable mean were greater than absolute mean. The findings in hypotheses testing showed significant association between difference mean dependent variable and independent variables. Researcher was suggesting TM in future would use again telemarketing to promote Streamyx package. But, telemarketing must be integrated or mix with other promotional tools